Circular RNA as Diagnostic and Prognostic Biomarkers in Hematological Malignancies:Systematic Review - Liyun Gao PhD; Junfei Fan BM; Jiayin He BM; Wenyan Fan MD; Xiangxin Che PhD; Xin Wang MD; Chunhua Han BM (Technology in Cancer Research & Treatment)
Objectives: While various serum and tissue biomarkers have been explored for tumor diagnosis, the sensitivity and specificity have not yield optimal results. Circular RNAs (circRNAs) are more stable, conserved, and tissue-specific than linear RNA. Recent reports indicate that circRNAs could serve as potential biomarkers in the diagnosis or/and prognosis of tumors. In this study, we systematically examined the relationship between circRNA expression and diagnostic and prognostic outcomes in patients with hematological tumors. Methods: We searched several databases, including Google Scholar, MEDLINE, Scopus, PubMed, Embase, ScienceDirect, Ovid-Medline, Chinese National Knowledge Infrastructure, WanFang and SinoMed, with a cutoff date of June 12, 2024. The study protocol was PROSPERO (CRD42020188627). Result: A total of 73 studies were included in our review, comprising 39 diagnostic studies and 65 prognostic studies. Clinical parameters were assessed based on pooled adds ratios and 95% confidence intervals (CIs). Overall survival (OS) was evaluated using hazard ratios (HRs) and 95% CIs. The pooled area under the curve was 0.86, indicating the potential to identify hematological tumor patients, with sensitivity and specificity of 79% each. The diagnostic score for circRNAs related to hematological malignancies was 2.12. Notably, different hematological malignancies subgroups displayed varying prognoses. Specifically, lymphoid leukemia circRNA showed a negative impacct on prognosis (HR = 1.25, 95% CI: 1.10-1.43, P < 0.001). Conclusion: Our findings provide compelling evidence that circRNA may be serve as a promising alternative for the diagnosis and prognosis of hematological tumors.